In situ chemical oxidation of ciprofloxacin by activated peroxymonosulfate using nanometric MnOOH: investigation of operational parameters and changes on the catalyst surface - Núñez de la Rosa, Yeison Neder (2023)
Nanometric MnOOH compound was synthesized by a green approach, characterized, and used to remove ciprofloxacin (CIP) antibiotic by in situ chemical oxidation using peroxymonosulfate (PMS). The effects of varying concentrations of MnOOH, PMS and pH, on morphological, structural, chemical, and electrochemical changes were studied during and after the experiments. The CIP molecule was completely oxidized and partially mineralized (~ 60%) after 6 h under acidic conditions. The mechanism of CIP degradation was induced by PMS activated oxidants (HO• and 1O2) and, to a lesser extent, directly on the surface of MnOOH. The latter process was evidenced by transmission electron microscopy showing the formation of an amorphous shell (MnOx) over MnOOH crystallites, as verified using X-ray photoelectron spectroscopy and the subsequent increase of the charge transfer resistance that hindered a further electron transfer to the PMS oxidant. Such behavior is recoverable when using a freshly prepared PMS solution.